Did the Days of Culture Nurture the Expenditure on Motion Pictures? - Lee, Jongyearn (KDI School of Public Policy and Management, 2022)
In Korea, since 2014, the last Wednesday of every month has been designated as 'Day of Culture (DoC)' on which discounts about half the normal price are applied to movies. This study empirically analyzes the differences in the number of audience and their expenditure before and after the introduction of the DoC. To this end, we construct panel data using daily movie screening data by 16 regions in the country. Estimation results applying difference in differences models reveal that the DoC has a statistically significant positive effect on both revenue and audience with the average treatment effect of 34.0 percent and 43.7 percent, respectively. Moreover, no evidence of cannibalization in the sense that no statistically significant decreases in revenue and audience on last Tuesday and Thursday of a month after the introduction of the DoC is found. Overall, estimation results suggest that the DoC creates the new demand for movies and expands opportunities for cultural enjoyment without any budgetary subsidy.
Keywords: Movies; Cinema Demand; Movie Ticket Discount; Cannibalization; Difference in Differences